Sexual Dimorphism Of The Sacrum In South Indian Population Using Mri - ABHIMANYU PRADHAN,; SUSHILYADAV, (International Journal of Pharma and Bio Sciences, 2015)
MRI plays a significant role in modern forensic anthropology to solve certain queries of legal / public concern. The objective of our study was to determine the sexual dimorphism of the first sacral vertebra (S1) in south Indian adults and to compare the differences in sacrum measurement of south India with literature. MRI of lumbo-sacral region was performed on 25 male and 25 female patients who were referred by treating doctor. Measurements were performed on T2 weighted mid-sagittal image. The dimensions measured were anterior height (AH), posterior height (PH), Superior diameter (SD) and inferior diameter (ID) of body of first sacral vertebra. The mean of AH, PH, SD and ID in male was 28.164±2.05 mm, 21.988±2.60 mm, 31.924±2.28 mm, 20.096±3.34 mm and in female it was 28.896±3.28 mm, 20.868±2.59 mm, 30.224±1.57 mm, 17.7±3.27 mm respectively. Also the mean lumbo-sacral angle (LSA), sacral base angle (SBA) and anterior sacral angle (ASA) were also measured which were 53.24±6.48º, 38.6±6.65º and 61.52±7.04º for male respectively and in female it was 61.28±8.68º, 41.8±6.07º and 55.2±9.07º respectively. Also the Indices (Index 1 and index 2) were calculated. The mean of Index 1 and Index 2 in male was 63.069±10.318 and 78.291±9.179 and in female it was 58.534±9.979 and 72.527±7.648 respectively. The measurements of S1 showed higher values in males than female in all of the investigated parameters, except for Anterior Height, lumbo-sacral angle & Sacral base angle. Therefore the body of the first sacral vertebra (S1) is found to be highly significant for determination of sex.